2022
DOI: 10.3389/fmed.2022.1001411
|View full text |Cite
|
Sign up to set email alerts
|

Low high-density lipoprotein cholesterol levels predicting poor outcomes in patients with hepatitis B virus-related acute-on-chronic liver failure

Abstract: BackgroundLipid profile disorders frequently occur in patients with advanced liver diseases. High-density lipoprotein cholesterol (HDL-C) levels decrease rapidly during acute conditions of some diseases, and HDL-C levels may be related to mortality in patients with hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF).Materials and methodsA retrospective cohort study was conducted on 200 subjects with HBV-ACLF. The patients were separated into non-survivors and survivors according to their 28-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Moreover, it has been found that hemoglobin could not only identify individuals at high risk of developing ACLF but also serve as a strong predictor in the survival rate of patients with cirrhosis, 47 poor outcomes in HBV-ACLF patients, low high-density lipoprotein cholesterol levels also played an important role in the pathophysiology of systemic in ammation driving the onset of ACLF. 49,50 Consistent with these ndings, our study also found that HDL-C < 0.5 mmol/L was a robust predictor for ACLF progression.…”
Section: Main Ndingssupporting
confidence: 86%
“…Moreover, it has been found that hemoglobin could not only identify individuals at high risk of developing ACLF but also serve as a strong predictor in the survival rate of patients with cirrhosis, 47 poor outcomes in HBV-ACLF patients, low high-density lipoprotein cholesterol levels also played an important role in the pathophysiology of systemic in ammation driving the onset of ACLF. 49,50 Consistent with these ndings, our study also found that HDL-C < 0.5 mmol/L was a robust predictor for ACLF progression.…”
Section: Main Ndingssupporting
confidence: 86%
“…Importantly, this new scoring model fills a gap in predictive models specific to ACLF triggered by HEV infection. However, this does not mean that dyslipidemia is related only to the disease caused by HEV, as previous studies have shown that lipids or their metabolic disorder were associated with stratification of severe hepatitis diseases in other cohorts [ 15 , 29 , 30 ] and have indicated poor prognosis [ 31 , 32 ]. In contrast, dyslipidemia may be the common pathophysiological response of ACLF.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a previous study found hypercholesterolemia was associated with well-preserved hepatic function and decreased mortality in patients with cirrhosis ( 32 ). On the other hand, a recent study showed that HBV-ACLF patients with lower high-density lipoprotein cholesterol level had a worse prognosis than those with higher HDL-C levels ( 33 ). Increased age also raises the risk of mortality due to a higher incidence of comorbidities and poor hepatic regeneration in response to acute insults ( 34 ).…”
Section: Discussionmentioning
confidence: 99%